Oriented Aggregation: Formation and Transformation of Mesocrystal Intermediates Revealed - Yuwono, Virany M; Burrows, Nathan D; Soltis, Jennifer A; Penn, R. Lee (Journal of the American Chemical Society, 2010)
Oriented aggregation is a special case of aggregation in which nanocrystals self-assemble and form new secondary single crystals. This process has been suggested to proceed via an intermediate state known as the mesocrystal, in which the nanocrystals have parallel crystallographic alignment but are spatially separated. We present the first direct observations of mesocrystals with size and shape similar to product oriented aggregates by employing cryo-TEM to directly image the particles in aqueous suspension. The cryo-TEM images reveal that mesocrystals not only form but also transform to the final single crystal product while in the dispersed state. Further, high-resolution cryo-TEM images demonstrate that the mesocrystals are composed of spatially separated and crystallographically aligned nanocrystals.